Body Mass Index and Postoperative Lumbar Pain Relief Following Surgery for Degenerative Lumbar Spine Disease: A Correlative Study - Rini Martina Siallagan; Enny Probosari; Happy Kurnia Brotoarianto; Siti Fatimah Muis; Etisa Adi Murbawani (PT BMW Journal Sejahtera, 2025)
Background: The prevalence of obesity and overweight is consistently rising. An increase in body mass index (BMI) above the normal range heightens the risk of chronic diseases, including musculoskeletal conditions such as lumbar degeneration and low back pain. The association between elevated BMI and postoperative lumbar pain remains debated. Objective: This study aims to assess the correlation between BMI and the improvement of postoperative lumbar pain. Methods: In this correlational study, 48 adults meeting specific inclusion and exclusion criteria were observed at a spine surgery clinic in Semarang, Central Java, Indonesia. BMI was calculated by dividing weight (kg) by height squared (m²). Pain levels were assessed using a visual analogue scale (VAS). The study controlled for variables such as age, gender, diabetes mellitus, osteoporosis, and type of surgery. Results: A positive correlation exists between increased BMI and elevated pain scale scores post-lumbar surgery in patients with lumbar degeneration (r = 0.654, p = 0.001). Additionally, the type of surgery and the presence of osteoporosis were found to correlate with pain levels. Conclusion: Patients with higher BMIs exhibited more pronounced postoperative pain compared to those with lower BMIs.